Counseling for Victims of Dating Violence with Emotional Freedom Technique: Single Case Research Design - Azizah, Mila Adela Nurul; Sugara, Gian Sugiana; Rahimsyah, Anandha Putri (Jurnal Konseling dan Pendidikan, 2024)
Dating violence is a phenomenon that can have serious consequences. Individuals who experience dating violence often face psychological challenges, including depression, anxiety, emotional trauma, and difficulties in forming healthy relationships in the future. This study aims to evaluate the effectiveness of Emotional Freedom Technique (EFT) counseling in improving psychological well-being among victims of dating violence. The research utilized a single-case design with an A-B-A format. The participant in this study was an individual with a moderate level of dating violence and low psychological well-being. The intervention consisted of four EFT counseling sessions. Data were collected before, during, and after the intervention. Visual analysis of the results indicated a significant improvement in the participant's psychological well-being and a reduction in symptoms related to dating violence. These findings suggest that Emotional Freedom Technique (EFT) counseling has the potential to be an effective intervention approach for victims of dating violence.